PERENCANAAN SISTEM TRANSMISI ALAT PENIRIS PADA MESIN PENGERING HELM - Samhuddin, Samhuddin; Hasbi, Muhammad; Jamiluddin, Jamiluddin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
A helmet drying machine is a device used to dry a helmet in a relatively short time. This helmet dryingmachine is divided into two parts namely: slicer/extortion machine and dryer. This slicer/squeezer machineserves to reduce the water content contained in the helmet up to 60-80%. In planning theoretically discussthe main components of the slicer transmission system on the helmet drying machine that determines: thediameter of pulley, the rotation ratio of the pulley, the shaft axis distance, the shaft diameter of the pulley II,and the bearing number. From the calculation results obtained as follows: 0.25 HP motor crusher power,electric motor rotation 1400 rpm, diameter pulley I 65 mm, diameter pulley II 130 mm, rotation ratio at 1:2pulleys, distance between the axis 251.32 mm axis, the diameter of the shaft on the pulley II 20 mm, and thenumber of open type 6004 bearings.Keywords: transmission system, pulleys and belts, shaft and bearing.